Internet control and disinformation across regime types during and after the Covid‐19 crisis - Kneuer, Marianne; Schünemann, Wolf J.; Bahms, Giulia (Politics and governance, 2024)
The unprecedented scale of mitigation measures taken by governments during the Covid-19 pandemic raised concerns about if and to what extent democracy would be affected. Empirical accounts show that media freedom was the most vulnerable. This article concentrates on interference in digital media, as attacks on the digital realm during the pandemic were particularly harmful given that media activity moved from print to online all over the world. This large-n study makes various important contributions. Firstly, it uncovers whether regime types differ in their reactions to the Covid-19 pandemic regarding the digital media sector. Secondly, it takes a diachronic approach and examines the period before 2020, during the pandemic in 2020 and 2021, and after the pandemic (2022–2023). This longitudinal exploration enables us to make nuanced statements about the post-Covid-19 developments in digital media. Thirdly, the analyses take into account different degrees of measures: less and more repressive as well as disinformation strategies. The results add value to the debate because they demonstrate that all regime types, including democracies, resorted to control mechanisms during the Covid-19 pandemic. Equally relevant is the behavior of these regimes after the pandemic: While democracies by no means cut back on all measures, autocracies did not strengthen all measures. Most remarkably, full democracies are the only regime type where governments increasingly engaged in disinformation after the pandemic. Thus, an important finding is that the pandemic did not constitute a catalyzing event for all regime types to the same extent. But the most worrisome effects are associated with the democracies.